2020
DOI: 10.1002/cche.10269
|View full text |Cite
|
Sign up to set email alerts
|

Development of wall material for the microencapsulation of natural vanilla extract by spray drying

Abstract: Background and objectives The aim of this study was to develop a wall material using rice starch (Oryza sativa) to optimize the microencapsulation of vanilla extract by spray drying. Native starch rice was hydrolyzed, succinated, extruded, and characterized. Findings The peak viscosity of modified starches was reduced from 3,875 cP to <100 cP by effect of the modification step. Native starch was gelatinized by extrusion according to gelatinization enthalpy (∆H J/g). Natural vanilla extract was encapsulated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…The average size of the granules was 4.64μm ± 1.26 for M1, 5.13μm ± 1.55 for M2 and 4.66μm ± 1.59 for M3, and a similar average size was observed between the three samples. The size of the microcapsules was smaller than that of other encapsulates obtained with modified rice starch with average values of 8.12 ± 3.92 μm [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 86%
“…The average size of the granules was 4.64μm ± 1.26 for M1, 5.13μm ± 1.55 for M2 and 4.66μm ± 1.59 for M3, and a similar average size was observed between the three samples. The size of the microcapsules was smaller than that of other encapsulates obtained with modified rice starch with average values of 8.12 ± 3.92 μm [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 86%
“…Estos métodos consisten en limitar el crecimiento hasta tasas mínimas llamada "conservación por lento crecimiento" (Hernández-Leal et al, 2020) o a la supresión total del metabolismo celular conocida como "crioconservación" (Hernández-Ramírez et al, 2020). Dentro de las ventajas de las estrategias biotecnológicas se encuentra el poco espacio requerido para el establecimiento de vitro plantas, reducción en trabajo mecánico y manipulación del material vegetal, salvaguardando su integridad e inocuidad y permitiendo así el mantenimiento de bancos de germoplasma eficientes y funcionales (Nhut 2022;Engelmann & González-Arnao, 2013).…”
Section: Conservación De Vanilla Planifoliaunclassified
“…Existe una gran diversidad de técnicas de crioconservación, como la inmersión en nitrógeno líquido, deshidratación por medio de agentes osmorreguladores, encapsulación y vitrificación, todo en dependencia de la especie y órgano(s) que se deseen conservar (semillas, embriones cigóticos, muestras de tejidos, yemas apicales, meristemos, etc.) (González-Arnao et al, 2020;Calva-Estrada et al, 2018;Ocampo-Salinas et al, 2020;Sakai, 1995;Panis, 1995, González-Arnao et al, 2009. Se ha estudiado el almacenamiento seguro de ápices de vainilla mediante técnicas basadas en la vitrificación, como es el caso de la técnica de Gota-Vitrificación (G-V) (González-Arnao et al, 2009), donde se experimentó en las distintas etapas que implica la técnica, sin embargo la combinación que resultó con mayores índices de regeneración fue empleando un pre acondicionamiento utilizando medio de cultivo MS suplementado con sacarosa (0,3 M) durante un solo día, un tratamiento de carga también con sacarosa 0,4 M en combinación con el glicerol 2 M y la solución vitrificadora PVS3 [50% (w/v) de glicerol + 50% (w/v) de sacarosa], durante 30 minutos de exposición, manteniendo a los tejidos en total oscuridad durante una semana, para favorecer su recuperación.…”
Section: Crioconservaciónunclassified
“…Spherical particles are obtained, which benefits the conservation and application of the powders in different products. Additionally, in most cases, spray drying is the method of choice due to its ease of scaling up and low operating costs, compared to freeze drying [ 30 , 31 , 32 ]. Moreover, an efficiency of 86.2% has been reported for the microencapsulation of natural vanilla extract using rice starch as wall material using spray drying has been reported [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in most cases, spray drying is the method of choice due to its ease of scaling up and low operating costs, compared to freeze drying [ 30 , 31 , 32 ]. Moreover, an efficiency of 86.2% has been reported for the microencapsulation of natural vanilla extract using rice starch as wall material using spray drying has been reported [ 31 ]. Moreover, it has been reported that heat pumps and nitrogen can be used on yield powders obtained from vanilla ethanolic extract closer to the 80% [ 32 ].…”
Section: Introductionmentioning
confidence: 99%